The Role of Platelet-Rich Plasma (PRP) in Enhancing IVF Success in Women With Ovarian Insufficiency: A Cohort Study - Zahra Mohammad Alipour; Farahnazsadat Ahmadi; Sina Mohajernoei; Roghaye Gharaei; Nazanin Hojjati; Elham Shirali; Firouzeh Akbari Asbagh (Acta Medica Iranica)
Ovarian insufficiency is a significant cause of infertility in women, with limited effective treatment options. Platelet-Rich Plasma (PRP), rich in concentrated growth factors, has shown regenerative potential in various medical fields. However, its efficacy as an adjunct in infertility treatment, particularly in women with ovarian insufficiency, remains unclear. This study investigates whether PRP administration improves the success of IVF cycles in this specific population. This cohort study followed women with ovarian insufficiency undergoing IVF at a fertility center. Participants were divided into two groups: the intervention group, which received PRP alongside the standard IVF protocol, and the control group, which received only the standard protocol. Data collected included patient demographics, hormonal levels, number and quality of retrieved oocytes, fertilization rates, embryo quality, and pregnancy outcomes. The primary outcome was IVF success, defined by clinical pregnancy rates. Secondary outcomes included hormonal changes, oocyte quality, and embryo development. Statistical analysis utilized descriptive statistics, chi-square tests, and t-tests to compare outcomes between groups. PRP administration led to significant reductions in FSH levels (P<0.001) and marked increases in AMH levels and antral follicle count (AFC) (P=0.001 and P<0.001, respectively). The number of oocytes, mature MII oocytes, and Grade A embryos also improved significantly (P ranging from 0.004 to 0.017). Although the increase in Grade B embryos was not statistically significant, it was higher post-PRP. Chemical pregnancies occurred in 25% of participants, with 20.83% resulting in clinical pregnancies, including 2.1% spontaneous pregnancies. PRP significantly enhanced ovarian reserve markers (FSH, AMH, AFC), oocyte quality, and embryo development, translating into improved fertility outcomes. The findings suggest that with longer follow-up and larger sample sizes, PRP could be validated as a promising adjunctive therapy for women with ovarian insufficiency undergoing IVF. These results align with prior research and highlight PRP’s potential to advance reproductive outcomes in this challenging patient population.